2009
DOI: 10.1007/s00167-009-0957-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two minimally invasive implantation instrument-sets for total knee arthroplasty

Abstract: Several choices of instrument systems are available for minimally invasive surgical approaches. There are reports that one alternative, the quadriceps sparing, side-cutting instrumentation, results in diminished implantation accuracy. A total of 108 patients were randomized to undergo TKA either using side-cutting implant instrumentation (Group A) or anterior-posterior mini-incision instrumentation (Group B). All TKAs were operated on with a minimal invasive, mini-midvastus surgical approach. 50% of the TKAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…There was distinct improvement in all patients after TKA, therefore differences between the groups are difficult to determine with our data. The lack of improvement in early clinical outcomes with patientspecific instrumentation is in accordance with other minimally invasive techniques combined with navigation [19,28,41]. Similar to our findings, Pietsch et al [41] conducted a randomized clinical trial of 80 patients divided into conventional instrumentation and patient-specific instrumentation groups and found no difference in the Knee Society score at 3 months.…”
Section: Discussionsupporting
confidence: 89%
“…There was distinct improvement in all patients after TKA, therefore differences between the groups are difficult to determine with our data. The lack of improvement in early clinical outcomes with patientspecific instrumentation is in accordance with other minimally invasive techniques combined with navigation [19,28,41]. Similar to our findings, Pietsch et al [41] conducted a randomized clinical trial of 80 patients divided into conventional instrumentation and patient-specific instrumentation groups and found no difference in the Knee Society score at 3 months.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have shown that the complication rates with MIS for TKA were significantly higher than those with standard TKA. [ 14 26 ] In this study, there were 3 instances of complications in the m-QS group and only 2 in the MMP group, which indicates that the difference between the two groups is not significant. None of the patients experienced any major complications.…”
Section: Discussionmentioning
confidence: 69%
“…The operation is believed to have an intraoperative risk of fracture at the surgical site, damage and rupture of the ligaments or muscles, insufficient removal of cement or bone fragments, skin necrosis due to severe traction, increased chance of infection, improper fixation of implants, and inappropriate implant alignment, all of which have a negative impact on the long-term clinical results, according to some research. 11 12 13 14 15 …”
Section: Discussionmentioning
confidence: 99%